Analisis Faktor Kepuasan Konsumen Melalui Value Chain dalam Memperoleh Keunggulan Bersaing Perusahaan Batik - Anggoro, Okky Priyo; , Ahmad Kholid Al Ghofari, ST. MT; , Ida Nursanti, ST., M.Eng.Sc (2016)
Creative industries have a significant economic contribution to the economy in Indonesia. Creating a better business climate, as the center of innovation and creativity that the creation of a positive social impact, and strengthen national identity. Value chain is a way in which companies can achieve profitability evaluate and exploit in any activity for best results. The purpose of this study is to identify the factors that affect and support the value chain in Batik Industry Sub Sondakan Laweyan District of Surakarta in improving customer satisfaction. Describing the order or position factor (activity) value chain in order to gain a competitive advantage batik company in increasing customer satisfaction. The data collection was done by distributing questionnaires, interviews and doing the documentation on the batik industry in village districts Sondakan Laweyan Surakarta. Data analysis was performed using analysis Normality (Kolmogrof Smirnov or Man Whitney) and relationship analysis (Spearman Rank Correlation). Based on research conducted in Batik Industry Sub Sondakan Laweyan District of Surakarta showed 6 variables in each indiktor Marketing and sales, tecnology development and procurement that can support value chain factors or activities are influential in increasing the competitive advantage of batik company in increasing customer satisfaction.